2012
DOI: 10.5506/aphyspolb.43.2237
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Electromagnetism becomes a nonlinear theory having (effective) photonphoton interactions due at least to electron-positron fluctuations in the vacuum. We discuss the consequences of the nonlinearity for the force felt by a charge probe particle, and compare the impact of Euler-Kockel QED effective nonlinearity to the possibility of Born-Infeld-type nonlinearity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Strong electromagnetic fields have been of interest for quite some time (see e.g. [24][25][26]) and can be applied in different contexts [27]. We have demonstrated that going from Maxwell's electrodynamics to the Euler-Heisenberg theory, the strong electric field will be reduced automatically far below the pair production threshold, at least as far as the energy content of the field is concerned.…”
Section: Discussionmentioning
confidence: 96%
“…Strong electromagnetic fields have been of interest for quite some time (see e.g. [24][25][26]) and can be applied in different contexts [27]. We have demonstrated that going from Maxwell's electrodynamics to the Euler-Heisenberg theory, the strong electric field will be reduced automatically far below the pair production threshold, at least as far as the energy content of the field is concerned.…”
Section: Discussionmentioning
confidence: 96%
“…In ultrarelativistic nucleus-nucleus collision, a pulsed and strong magnetic field is generated, and the space-time geometry is nontrivial due to expansion and flowing fluids (that may cause horizon formation or an acoustic metric; see Refs. [21,22] for related discussions). Finally, although for lower dimensionality the magnetic field and the curvature cooperate (rather than compete), the present discussion may be of relevance in the context of strongly coupled layered materials, where curvature can be generated locally by the insertion of defects.…”
Section: Curvature Induced Chiral Gap and Magnetic Inhibitionmentioning
confidence: 99%
“…For example consider a 50GeV beam (γ = 10 5 ). For a laser beam propagating against the electron beam, its field in the frame of reference of the electrons, will be enhanced by γ = 10 5 This should bring the field acting in the rest frame of the electron to a level much higher than the critical intensity [13,14,15]. 3.…”
Section: Bridging the Gap; All The Way To The Schwinger Intensity Regimementioning
confidence: 99%